2021
DOI: 10.14569/ijacsa.2021.0120802
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Relationship between Exploratory Behavior and Consumer Values using Eye Tracking Gaze Data

Abstract: In recent years, the popularity of e-commerce has witnessed a significant uptick. Physical apparel stores need to implement measures that focus on the behavioral experience of shopping at physical stores, a trait that e-commerce lacks. The purpose of this paper is to clarify the relationship between customer values and product search behavior and proposed product placement and customer service methods based on their values. We used questionnaire data on the values of customer purchasing to perform factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous EEG mapping studies have found increased beta power and decreased alpha and delta/theta power in deaddictive alcoholic patients, compared to normal controls. Since slow activity is considered inhibitory, fast beta activity excitatory and alpha activity an expression of normal brain function, the desynchronised low-voltage fast patterns can be translated as CNS hyperexcitation [30], [31].…”
Section: A Eeg and Substance Addiction 1) Alcoholmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous EEG mapping studies have found increased beta power and decreased alpha and delta/theta power in deaddictive alcoholic patients, compared to normal controls. Since slow activity is considered inhibitory, fast beta activity excitatory and alpha activity an expression of normal brain function, the desynchronised low-voltage fast patterns can be translated as CNS hyperexcitation [30], [31].…”
Section: A Eeg and Substance Addiction 1) Alcoholmentioning
confidence: 99%
“…Opinions as to the cause of these EEG changes in alcoholics show that incoherencies in brain function, particularly in frontal parts of the brain, may be participating in the development of alcoholism [5], [30], [31]. This is documented by a variety of studies: beta activity has been linked to the combination of the two pre-morbid factors of childhood behaviour disorders and paternal alcoholism.…”
Section: A Eeg and Substance Addiction 1) Alcoholmentioning
confidence: 99%
See 1 more Smart Citation